The Influence of Corporate Governance and Profitability on Firm Value with Corporate Social Responsibility as a Moderating Variable in Companies Listed on the Indonesia Stock Exchange (IDX) - Ernaria Lamsari; Tubagus Ismail; Hendrian Hendrian (International Journal Labs, 2026)
A company's value is an important indicator that reflects the market's perception of the company's performance and sustainability. In recent years, the role of corporate governance and profitability in increasing corporate value has received considerable attention; however, empirical research results still show inconsistent findings, especially when corporate social responsibility (CSR) is taken into account. This study aims to analyze the influence of corporate governance and profitability on company value and examine the role of CSR as a moderating variable. The study employs a quantitative approach using secondary data from manufacturing companies listed on the LQ45 index of the Indonesia Stock Exchange during the observation period. Company value is measured using Tobin's Q; corporate governance is proxied through governance mechanisms; profitability is measured by return on assets; and CSR disclosures are assessed using the Global Reporting Initiative (GRI) index. Data analysis was carried out using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that corporate governance and profitability have a positive effect on company value. In addition, CSR has been shown to strengthen the relationship between corporate governance and company value, while its moderating effect on profitability is comparatively weaker. These findings suggest that CSR is not merely symbolic but serves as a strategic mechanism that enhances market valuation when supported by effective governance.